Acham que somos alienados: o rock na imprensa do litoral do Piauí nos 1970-80 - Moura, Gustavo Silva De [UNIFESP] (2019)
The present work investigates the musical/behavioral rock phenomenon on the coast of Piauí in the 1970s and 1980s, through the local press, more precisely: Folha do Litoral, A libertação e Jornal Inovação. It is intended to examine how newspapers defined and approached rock in its pages. The aim, has the objective explore the propagation ways of the musical style in the region, reaching the local youth, considering the effervescence of the Brazilian music industry in the 1970s and its consolidation in the 1980s. The approach that local press has assigned to rock allows to problematize aspects of the political, social and cultural context of the period, in a locality where this phenomenon needs investigations. This is a little studied at the postgraduate level when it refers to Brazilian Northeast and unpublished on the coast of Piauí.